Participatory Management Strategies of Village Health Volunteers and Community Leaders in the Prevention and Surveillance of the Coronavirus Disease 2019 (COVID-19), Vibhavadi District, Surat Thani Province - Sadadkhan, Ayab (Rajapark Journal, 2023)
The objective of this article was to study the participatory management strategies of village health volunteers and community leaders in prevention and surveillance of the outbreak of Coronavirus 2019 (COVID-19). A questionnaire was used as a quantitative research tool. The frequency distribution statistical data were analyzed and converted to percentage, mean, standard deviation, chi-square statistic, t-test analysis, and one-way analysis of variance. The qualitative research was analyzed using in-depth interviews, observations, and focus groups, together with information from research papers, theories, and concepts, to obtain comprehensive information. The research results were presented using both descriptive and analytical methods. The results of the study showed that the sample had a reason for participating as village health volunteers and community leaders because they wanted to build their self-esteem: 26.1%; followed by community engagement at 24.1%; needing to develop themselves at 17.4%; having a voluntary mind at 16.6%; and caused by social support at 15.8%, respectively. When considering the opinions about the participatory management of village health volunteers and community leaders in each aspect of prevention and surveillance of the COVID-19 outbreak, it was found that the sample group had opinions on the benefits, decision-making, evaluation, and performance at a high level, with mean values of 3.89, 3.86, 3.84, and 3.81, respectively.